Farming of The Future: How Tech Companies Triggers A Farming Revolution - Wardhana, Muhammad Zaky Nur Fitra (Ridwan Institute, 2023)
Advances in technology in communication currently have a significant change throughout all sectors. Agriculture especially in Indonesia has a big potential to apply this 4.0 technology that will drive a significant output and productivity in crops production. The world’s population is projected to rise from 7.4 billion currently to 8.1 billion in 2025, according to the UN’s Food and Agriculture Organization. The UN food agency’s latest annual agricultural outlook, produced alongside the OECD, forecast that 80% of the increase in crop output needed to feed this population would come from yield improvements. The main idea of this paper is twofold: the first one is to Understand how agriculture 4.0 could take place and improve the productivity of a crops production with a descriptive approach. And the second one is to Understand what the gaps of Indonesia as 3rd are ranked rice producer in the world to deploy the agriculture 4.0